Comparative evaluation of micron- and nano-sized intracanal medicaments on penetration and fracture resistance of root dentin – An in vitro study - Sireesha, Abburi; Jayasree, R.; Vidhya, Sampath; Mahalaxmi, Sekar; Sujatha, V.; Kumar, T.S. Sampath (International journal of biological macromolecules, 2017)
•This study evaluated the depth of penetration of calcium hydroxide, chitosan and their nanoforms.•The effect of these medicaments on the fracture resistance of endodontically treated roots and their antimicrobial efficacy on E. faecalis was also evaluated.•Nanoparticles penetrated to greater depths into dentinal tubules and exhibited significantly greater antimicrobial efficacy against E. faecalis.•While calcium hydroxide reduced fracture resistance of teeth, chitosan showed better fracture resistance values when used as an intracanal medicament.•Nanoforms of calcium hydroxide and chitosan could serve as better intracanal medicaments. Intracanal medicaments play a vital role in disinfection of root canal system. The aim of this study was to evaluate intratubular penetration and fracture resistance of roots filled with micron- and nano-sized intracanal medicaments: calcium hydroxide (CH), nanocalcium hydroxide (NCH), chitosan (CS) and nanochitosan (NCS). Their antibacterial effect on E. faecalis was tested using agar diffusion method. NCH and NCS were prepared by precipitation method and ionic crosslinking respectively. NCH and NCS particles were spherical, with an average particle size of 102±11.3nm and 130±17.6nm respectively. The medicaments were filled in extracted human teeth. Depth of penetration of the medicaments into dentinal tubules at coronal (C), middle (M) and apical (A) thirds was measured. Fracture resistance of the teeth was evaluated after 1 week and 1-month intervals. NCH showed the highest depth of penetration (C ∼746.98μm, M ∼700.30μm, A ∼134.69μm). CS showed the highest fracture resistance, whereas no significant difference was found between other medicaments, at both the time intervals. NCH (8.07±0.06) and NCS (8.13±0.06) showed significantly higher zone of inhibition than CH (7.7±0.17) and CS (7.37±0.15). Under the conditions of this study, it can be concluded that NCH and NCS can be used as potential intracanal medicaments.